Impact of a short‐term exposure to tributyl phosphate on morphology, physiology and migratory behaviour of European eels during the transition from freshwater to the marine environment. Issue 2 (20th March 2013) - Privitera, Lucia; Aarestrup, Kim; Moore, Andy
Abstract Migrating silver European eels were exposed for 5 days in a laboratory to an environmental level of tributyl phosphate (TBP), tagged with acoustic transmitters and released below the Tange hydropower station, on the River Gudenaa, Denmark. The subsequent movements of the eels were monitored as they migrated through Randers Fjord and into the Kattegat Sea using an array of acoustic receivers. In laboratory‐based studies, exposure of eels for 5 days to a nominal concentration of 0.5 μg·l−1 TBP significantly affected plasma glucose concentration and reduced plasma levels of sodium and chloride both in freshwater and 3 days after transfer to saltwater. However, there were no mortalities when the eels were transferred to full strength sea water. Exposure to TBP did not appear to have a significant effect on the subsequent movements of the eels in the river or fjord. The eels moved rapidly through the fjord predominantly at night. The results of the study are discussed in relation to the impact of diffuse pollution on the behaviour and physiology of European eels.